Effect of Ronnel® on performance of feedlot steers - Riley, Jack G.; Tobyne, D. (Kansas State University. Agricultural Experiment Station, 2011)
We used 180 yearling Hereford and Angus x Hereford crossbred steers averaging 643 pounds in a 139-day, feedlot trial to evaluate steer performance when the systemic grub control pesticide Ronnel was fed at 5 levels; 1, 16, 32, 64 and 128 grams per ton of complete feed. Runnel increased daily feed intake an average of 2.5%; 64 grams/ton produced gains 8.5% faster and 5.8% more efficiently than the controls (0 Ronnel) and was the most beneficial dose. No significant differences were observed in carcass traits. This product is presently not cleared for use in feedlot cattle.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Performance; Steers; Feedlot